Transcranial doppler as screening method for sickling crises in children with sickle cell anemia: a latin America cohort study - Modolo, Gabriel Pinheiro [UNESP] (2022)
Background: Sickle cell anemia (SCA) is the leading cause of childhood stroke. We aimed to evaluate whether altered cerebral flow velocities, as measured by transcranial Doppler (TCD), are associated with vaso-occlusive complications in addition to stroke in pediatric SCA patients. Methods: We evaluated 37 children aged between 2 and 16 years with SCA who underwent screening for TCD between January 2012 and October 2018. Genotypic profiles and demographic data were collected, TCD examinations were performed during follow-up, and the presence of sickling crises was compared. Survival analyses were performed using simple frailty models, in which each predictor variable was analyzed separately in relation to the occurrence of a sickling crisis. Results: The variables related to sickle cell crises in the univariate analysis were peak systolic velocity (PSV) in the middle cerebral artery (MCA), hazard ratio (HR) 1.01 (1.00—1.02) p = 0.04; end-diastolic velocity (EDV) in the MCA, HR 1.02 (1.01—1.04) p = 0.01; time average mean maximum velocity (TAMMV) in the basilar artery (BA), HR 1.02 (1.00—1.04) p = 0.04; hemoglobin, HR 0.49 (0.38—0.65) p < 0.001; hematocrit, HR 0.78 (0.71—0.85) p < 0.001; leukocyte counts, HR 1.1 (1.05—1.15) p < 0.001; platelets counts, HR 0.997 (0.994—0.999) p = 0.02; and reticulocyte numbers, HR 1.14 (1.06—1.23) p < 0.001. Conclusions: Our results indicate PSV and EDV in the MCA and TAMMV in the BA as markers of risk for the occurrence of sickling crises in SCA.